HIKING/CAMPING EQUIPMENT RENTAL INFORMATION SYSTEM AT THE MARI MENDAKI GARUT SHOP - Aditya Putra Maulana (ADVANCE INFORMATICS RESEARCH JOURNAL, 2026)
Mature this , in development science and technology has many new media that can help delivery accurate , fast and reliable information​ reliable . Currently the internet has Lots utilized Good it is by companies , educational institutions , government . Various field information can presented by the internet including field economics , politics , social and culture. mari shop climb need A capable system​ processing information data rental with method make application rental android based and online rental so that everything the store offers can accessible to many people and more easy For attract customers. This is a number of method For create a shop let's climb the more growing , because will more known among public with internet media assistance . In the design system This There is a number of The steps to be designed include Flowcharts, Context Diagrams , Data Flow Diagrams , Entity Relationship Diagrams, and Database Tables. existence system information created , it is hoped can increase rental and expanding the market. With existence system information created , it is hoped can increase rental and expanding the market. From the results manufacturing system information rental outdoor hiking/camping equipment at the Let's Climb Garut shop this , then writer recommend For in the future application This can be updated again with add more features​ complete .